Battery Charger Regulator With Fully Controlled Rectifier 15 V/5 A On Uninterruptable Power Supply - Daud, Muhammad; Hasibuan, Arnawan; Shobirin H, Rizki; Al-Ani, Waleed Khalid Ahmed (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
Fully controlled rectifier and Battery Charge Regulator (BCR). BCR is the main unit of UPS ( Uninterruptable Power Supply ) equipment. The fully controlled rectifier has the function of supplying voltage directly to the BCR, and the BCR has the function of regulating the battery charge. Forced charging the battery at a constant voltage with a current that matches the life of the battery will have an impact on decreasing battery life, besides that it will have an impact on the efficiency of using the battery. Controlling the input voltage of the charging battery as a function of the battery voltage is regulated by the magnitude of the charging current flow. Charging the battery via BCR is adjusted to the battery voltage so that BCR can control it by adjusting the voltage to 13.5 V for High Voltage Disconnected (HVD) and 10.5 V for Low Voltage Disconnected (LVD). Based on the test results of the performance of the full control rectifier system and BCR on a 12 V battery with a capacity of 5 Ah, it shows that the output voltage is A fully controlled 12 V rectifier, the BCR can charge an empty internal battery in a few minutes with a current varying from 2 .1 A to 0.1 A.